Pendekatan Media Sosial Terhadap Aktivitas Dakwah Kalangan Milenial Di Era Digital - Nurhasanah Nurhasanah; Salwa Intan Fatikah; Silvy Aulia Arifah; Meity Suryandari (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Along with the times, da'wah has experienced significant development, starting from the number of followers, methods, strategies, and media which have now become a means of driving da'wah activities themselves. This is of course inseparable from the all-digital era, da'wah can be carried out in various media that are quite efficient, fast and easy. One of them is the existence of the internet which has been followed by the emergence of social media. Library research or also called literature review (literature research, literature review) was chosen as a systematic way to collect data and systematize pre-existing research. By using the analytical descriptive method, namely a study that seeks to describe, write, analyze, interpret existing conditions so as to reveal existing facts related to opportunities and challenges as well as new media da'wah strategies that rely on how social media works by going with the flow in the digital era. Da'wah methods play an important role in da'wah activities. A da'i must be observant and wise in choosing methods, because methods greatly affect the smoothness and success of da'wah. In this millennial era, a da'i must think of the right method to convey his da'wah message. So it is necessary to have a discussion regarding the method of delivering da'wah that is suitable for the millennial generation. The existence of social media, most teenagers tend to use this access not for positive purposes, but for negative things. Many of the teenagers are also in this all-digital era, do not understand even do not understand religion. Therefore, things like this must be prevented by influencing youth through positive content such as preaching. Da'wah content can be made as attractive as possible so that it can attract teenagers to want to watch it. As interspersed with content that motivates to be more active in learning and others. All da'wah content can be spread via YouTube, Tiktok, Instagram, Twitter, Facebook and other social media commonly used by teenagers. As interspersed with content that motivates to be more active in learning and others. All da'wah content can be spread via YouTube, Tiktok, Instagram, Twitter, Facebook and other social media commonly used by teenagers. As interspersed with content that motivates to be more active in learning and others. All da'wah content can be spread via YouTube, Tiktok, Instagram, Twitter, Facebook and other social media commonly used by teenagers.